Physicochemical Analysis of the Drinking Water of Al Gedarif City, Sudan - Abdel Daim, Zeinab J.; Abdel-Rahim, Awad M.; Babikir, Mohamed O. (Gezira Journal of Engineering and Applied Sciences, 2010)
In the present study the highest residual chlorine level (0.2) was detected in the city inlet and the circular line of the Atbara River sources. The taste, color and odor were found acceptable, although, the ground water is a bit salty and the raw water of the main stream of Atbara River, is always brown in color, specially in the autumn season. The highest turbidity value was recorded for the main stream of Atbara River, while, the maximum electric conductivity was found in Al Azasza boreholes. The total dissolved solids were greater in the ground water sources compared to that of the surface water sources. However, the total alkalinity  and  hardness  values  were  higher  in  the  ground  water  of  Al Azaza boreholes than that of all the other sources. On the other hand, the mineral contents (calcium, potassium, magnesium and sodium) were higher in the ground water. Fluorides, chlorides and bicarbonates were also higher in ground water. Similarly, were the contents of nitrates, nitrites and ammonia. However no carbonates were detected in Al Azaza and Abu Naja nor in Al Saraf dam raw water.